Unveiling Zieve's syndrome: A rare yet underdiagnosed complication of chronic alcoholic hepatitis - Kunal Agrawal; Sourya Acharya; Samarth Shukla; Preeti Mishra; Saket S. Toshniwal (Journal of Krishna Institute of Medical Sciences University)
Zieve's Syndrome (ZS), also known as hyperlipidemic jaundice, is a rare and intriguing clinical entity characterized by a unique constellation of symptoms, including hemolytic anaemia, jaundice, and transient hyperlipidemia. The aetiology of ZS primarily revolves around chronic alcohol abuse, although non-alcoholic causes have been reported. Syndrome is believed to result from alcohol-induced hepatotoxicity leading to hepatic steatosis, impaired lipid metabolism, and subsequent hemolysis and jaundice. Acanthocytes, or spur cells, are a distinct feature observed in some cases of ZS, particularly in the context of hemolytic anaemia. The clinical presentation typically includes symptoms of anaemia, such as fatigue and pallor, accompanied by jaundice and possibly hepatomegaly. Laboratory investigations often reveal elevated liver enzymes, hyperbilirubinemia, and elevated lipid levels, particularly triglycerides. In this case study, we present a 46-year-old male patient with a history of chronic alcoholism, who presented with chief complaints of yellowish discoloration of the eyes, extreme fatigability, and abdominal pain. Diagnosis of alcoholic hepatitis with ZS was confirmed, and appropriate management, including thiamine supplementation, intravenous fluids, and proton pump inhibitors, was initiated. The patient exhibited notable improvement following treatment, highlighting the efficacy of comprehensive intervention in such cases.